Space and Meaning: Symbolic Transformation of Boat in Bajau Dwelling Culture in Sainoa Island, Salabangka Archipelago - Ikram Ikram; Indah Widiastuti; Mohammad Zaini Dahlan; Nuning Yanti Damayanti; Ignatius Bambang Sugiharto (Sinektika: Jurnal Arsitektur, 2026)
This article aims to examine how the Bajau dwelling culture is maintained through the continuity and transformation of spatial symbolic structures derived from boat-based life. This study employs a qualitative interpretative approach to explore the Bajau dwelling culture through spatial symbolic analysis. The analysis includes: (1) Identifying spatial elements derived from boat structures; (2) Interpreting their symbolic meanings; and (3) Examining how these elements are maintained or transformed in permanent residences. Findings of this study reveal that the symbolic meaning of the boat in the Bajau dwelling culture has transformed over time. The boat is no longer understood solely as a house or means of transportation, but also functions in festival performances, tourism support, transportation, and contemporary art as a representation of Bajau identity. The transformation of Bajau dwelling culture is influenced by several factors, including sociological demands, education, government relocation proposals, social interactions with land-based communities, and modernization. However, despite the modernization of dwelling forms and materials Bajau on Sainoa Island, the symbolic structure of the boat remains embedded in the domestic spatial configuration. The spatial hierarchy is still recognizable in both sea- and land-based houses: the bow is the front room, the middle room is the family room and resting area, and the stern is the kitchen.